Odpowiedzi

Najlepsza Odpowiedź!
2010-03-28T20:34:04+02:00
-12-3x=-5x+4 (przerzucam)
-3x+5x=4+12
2x=16 | :2
x=8

czyli x=8
masz :
x+6=-2x+30
x+2x=30-6
3x=24 | :3
x=8

----------------------------------------------

7x+3=2x-17 (przerzucam)
7x-2x=-17-3
5x=-20| :5
x=-4

czyli x = -4
masz:
3x+8=2(2+x)
3x+8=4+2x
3x-2x=4-8
x=-4

----------------------------------------------

4(3x-1)=2(5x+6)
12x-4=10x+12 (przerzucam)
12x-10x=12+4
2x=16|:2
x=8

czyli x = 8
masz :
12-4+6+x=2x-6-4
-2+x=2x-6-4
x-2x=-6-4+2
-x=-8 | *(-1)
x=8

----------------------------------------------

; ))
2010-03-28T20:37:58+02:00
-12-3x=-5x+4
-3x+5x=4+12 (po przeniesieniu na drugą stronę znak zmienia się)
2x=16 / :2
x=8

przykład:
-10-2x=-4x+6
-2x+4x=6+10
2x=16
x=8

7x+3=2x-17
7x-2x=-17-3
5x=-20
x=-4

przykład:
10x+5=-15+5x
10x-5x=-15-5
5x=-20
x=-4

4(3x-1)=2(5x+6)
12x-4=10x+12
12x-10x=12+4
2x=16
x=8

przykład:
18x-8=16+8
18x-16x=8+8
2x=16
x=8
2010-03-28T20:52:02+02:00
-12-3x=-5x+4
-3x+5x = 4+12
2x = 16 /:2
x = 8
przykład:
2-2x = -4x +18
-2x+4x = 18-2
2x = 16
x = 8

7x+3=2x-17
7x-2x = -17-3
5x = -20 /:5
x = -4
przykład:
-5x-4 = -10x-24
-5x+10x = -24+4
5x = -20
x = -4


4(3x-1)=2(5x+6)
12x-4 = 10x+12
12x-10x = 12+4
2x = 16 /:2
x = 8
przykład:
2(6x-2) = 10x+12
12x-4 = 10x+12
12x-10x=12+4
2x = 16
x = 8